2022
DOI: 10.1111/dme.14821
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and the risk of neurodegenerative diseases in patients with diabetes: A meta‐analysis of population‐based cohort studies

Abstract: The association between metformin use and neurodegenerative disease (ND) onset remains controversial. In this systematic review and meta-analysis, we aimed to determine the relationship between metformin use and ND risk based on data from population-based cohort studies.Methods: Articles were systematically searched in PubMed, EMBASE and Cochrane Library databases. Pooled relative risks (RRs) with 95% CIs were obtained using a random-effects model. Subgroup analyses, sensitivity analyses and meta-regression we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…The results from a systematic review published in 2020 that was based on 23 comparisons of 19 studies and over 250,000 subjects concluded that there was no benefit associated with the use of metformin and for Parkinson's and, in fact, metformin may worsen the risk for Parkinson's [362]. In contrast, a 2022 systematic review and meta-analysis of 94,462 metformin users versus 100,330 non-users concluded that longterm (≥ 4 years) treatment with metformin was associated with a lower risk of neurodegenerative disease, and particularly in Asiatic populations [363].…”
Section: Metformin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The results from a systematic review published in 2020 that was based on 23 comparisons of 19 studies and over 250,000 subjects concluded that there was no benefit associated with the use of metformin and for Parkinson's and, in fact, metformin may worsen the risk for Parkinson's [362]. In contrast, a 2022 systematic review and meta-analysis of 94,462 metformin users versus 100,330 non-users concluded that longterm (≥ 4 years) treatment with metformin was associated with a lower risk of neurodegenerative disease, and particularly in Asiatic populations [363].…”
Section: Metformin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…A metaanalysis of the impact of metformin on neurodegenerative disease suggests that metformin use, and in particular longer term use of the drug, is associated with a reduced risk of neurodegenerative disease. 6 This is an important finding as it is rapidly implementable in clinical practicemetformin is universally available, is a lower-cost drug, has a well-established safety profile and an inclusive set of indications that mean that, contrary to new or experimental therapeutics, it can be delivered rapidly. Long-term randomised controlled trials would be beneficial but may not report for many years while implementing existing agents is more acceptable and feasible, though this must be accompanied by robust data collection to assess impact.…”
Section: E D I T O R I a L It's Complicatedmentioning
confidence: 99%
“…Neurodegenerative diseases, including Alzheimer's disease, Parkinson's disease, dementia and cognitive disorders are more common in people with diabetes and a portfolio of effective treatment strategies is required to meet the rising prevalence. A meta‐analysis of the impact of metformin on neurodegenerative disease suggests that metformin use, and in particular longer term use of the drug, is associated with a reduced risk of neurodegenerative disease 6 . This is an important finding as it is rapidly implementable in clinical practice—metformin is universally available, is a lower‐cost drug, has a well‐established safety profile and an inclusive set of indications that mean that, contrary to new or experimental therapeutics, it can be delivered rapidly.…”
mentioning
confidence: 99%
“…In addition, metformin use has been associated in observational studies with a reduced risk of developing tumors in patients with type 2 diabetes mellitus [10][11][12][13]. Meta-analyses have also shown that metformin use is associated with a reduced risk of tumorigenesis [14,15]. Diabetes is closely related to the prognosis of tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was also associated with an increased risk of some tumors [17,18]. Metformin use has been shown to be associated with better outcomes in cancer patients, and metformin use has been shown to prolong progression-free survival and overall survival [19,20] (14,18,19). Although some data suggest that metformin has an anticancer effect, some studies have questioned its anticancer effect, suggesting that metformin use is not associated with patient outcome [21].…”
Section: Introductionmentioning
confidence: 99%